2011
DOI: 10.1099/ijs.0.022038-0
|View full text |Cite
|
Sign up to set email alerts
|

Candida andamanensis sp. nov., Candida laemsonensis sp. nov. and Candida ranongensis sp. nov., anamorphic yeast species isolated from estuarine waters in a Thai mangrove forest

Abstract: Five strains (RV5T, RV140, R31T, RS17 and RS28T) representing three novel anamorphic ascomycetous yeast species were isolated by membrane filtration from estuarine waters collected from a mangrove forest in Laem Son National Park, Ranong Province, Thailand, on different occasions. On the basis of morphological, biochemical, physiological and chemotaxonomic characteristics, sequence analysis of the D1/D2 domain of the large-subunit rRNA gene and the internal transcribed spacer region and phylogenetic analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Members of the proposed genus originate from a diversity of sources (), but an ecological generalization does not seem possible in view of the small number of known specimens. Isolation substrates include a leg wound ( C. neorugosa ), faeces ( C. rugosa and C. catenulata ), sputum ( C. pseudorugosa ), blood ( C. mesorugosa ), rotten oak wood ( C. scorzettiae ), and estuarine water ( C. ranongensis ), as well as soil and spoiled food (Li et al, 2006; Middelhoven & Kurtzman, 2007; Am-In et al , 2011; Lachance et al , 2011; Paredes et al , 2012; Chaves et al , 2013). The present study adds three strains of a novel species isolated from rice leaf tissue and four strains of C. scorzettiae recovered from estuarine water, soil, and fruit flies.…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the proposed genus originate from a diversity of sources (), but an ecological generalization does not seem possible in view of the small number of known specimens. Isolation substrates include a leg wound ( C. neorugosa ), faeces ( C. rugosa and C. catenulata ), sputum ( C. pseudorugosa ), blood ( C. mesorugosa ), rotten oak wood ( C. scorzettiae ), and estuarine water ( C. ranongensis ), as well as soil and spoiled food (Li et al, 2006; Middelhoven & Kurtzman, 2007; Am-In et al , 2011; Lachance et al , 2011; Paredes et al , 2012; Chaves et al , 2013). The present study adds three strains of a novel species isolated from rice leaf tissue and four strains of C. scorzettiae recovered from estuarine water, soil, and fruit flies.…”
Section: Ecologymentioning
confidence: 99%
“…The species are known from a few isolates from clinical specimens, insects, rotting wood, dung, or spoiled food. Three more relatives not included in the monograph, Candida mesorugosa , Candida neorugosa and Candida pseudorugosa , have been isolated from clinical materials (Li et al , 2006; Paredes et al , 2012; Chaves et al , 2013) and another, Candida ranongensis , was found in a small number of estuarine water samples in Thailand (Am-In et al , 2011). Addition of new taxa did little to provide a more satisfactory placement of the clade from sequences of the D1/D2 domains of the large subunit rRNA gene.…”
mentioning
confidence: 99%
“…Thailand is a tropical country, rich in biodiversity in plants, animals, and microorganisms (bacteria, yeasts, and filamentous fungi); however, the microbial diversity, especially that of yeasts, has received less attention compared to the diversity of plants and animals. Only a few reports have been published to date on yeast diversity in natural habitats, for example, on the surface and tissue of plant leaves [22][23][24], the soils and peat soils in peat swamp forests [25,26], and water and sediment in a mangrove forest [27][28][29]. Fungi in marine environments, including yeasts, are far less studied than fungi in terrestrial environments, not only in Thailand but also all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Pichia spartinae from southeastern U. S. salt marshes and associated with the marsh grass Spartina alterniflora, (2,9,20,21), and various new species including some in the Saccharomyces clade have been described recently from mangroves confirming the yeast species richness of this biome (4,5,13,19). Yeasts of the genus Kluyveromyces have been found frequently in these environments.…”
Section: Scheffersomyces Spartinae Has Been Reported Under the Namementioning
confidence: 83%